DPP4 Inhibitors increase differentially the expression of surfactant proteins in Fischer 344 rats. (15th September 2014) - Schmiedl, A.; Grützner, D.; Hoffmann, T.; von Hörsten, S.; Stephan, M.
Abstract Aim Intact surface active agent (surfactant) composed of surfactant‐associated proteins (SPs) and lipids is necessary for respiration and prevents alveoli from collapsing. CD26, a transmembrane glycoprotein exerting dipeptidyl peptidase activity (DPP4), highly expressed in lung parenchyma, is involved in inflammatory processes. A pharmacological inhibition of DPP4 influenced not only the inflammation but also elevated the SPs. Thus, DPP4 inhibitors may be a novel drug for treatment of diseases with surfactant deficiency. Therefore, we tested firstly the hypothesis that DPP4 inhibitors increase the expression of SPs in healthy rats. Methods SP mRNA and protein expression were determined different times after nebulization of aerosolized DPP4 inhibitors [L‐isoleucine‐thiazolidide (L‐Ile‐Thia), L‐valine‐pyrrolidide (L‐Val‐Pyrr)], budesonide, saline or stereoisomers. Results Compared with negative controls (1) L‐Ile‐Thia as well as budesonide led to a significant higher and L‐Val‐Pyrr had the tendency to a significant higher expression of SP‐A mRNA 6 h after nebulization, (2) the expression of SP‐D mRNA increased significantly 6 h after nebulization with L‐Ile‐Thia and 3 and 6 h after nebulization with Val‐pyrr, (3) SP‐B mRNA levels showed significantly higher values 3 and 6 h after nebulization with L‐Val‐Pyrr, (4) protein levels of SP‐A, SP‐B and SP‐C were elevated significantly 6 h after nebulization with L‐Val‐Pyrr as well as with budesonide, and (5) phospholipids were also increased in response to DPP4 inhibition; the minimal surface tension was comparable. Conclusion DPP4 inhibition influence differently the expression of surfactant proteins in healthy rats and may be suitable to elevate surfactant synthesis in different diseases accompanied with surfactant deficiencies.